Transgenic zebrafish as a model for investigating diabetic peripheral neuropathy: investigation of the role of insulin signaling - Lee, Dong-Won; Park, Hae-Chul; Kim, Dong Hwee (Frontiers in Cellular Neuroscience, 2024)
Diabetic peripheral neuropathy (DPN), a complication of diabetes mellitus (DM), is a neurodegenerative disorder that results from hyperglycemic damage and deficient insulin receptor (IR) signaling in peripheral nerves, triggered by failure of insulin production and insulin resistance. IR signaling plays an important role in nutrient metabolism and synaptic formation and maintenance in peripheral neurons. Although several animal models of DPN have been developed to identify new drug candidates using cytotoxic reagents, nutrient-rich diets, and genetic manipulations, a model showing beneficial effects remains to be established. In this study, we aimed to develop a DPN animal model using zebrafish to validate the effects of drug candidates on sensory neuropathy through in vivo imaging during the early larval stage. To achieve this, we generated Tg (ins:gal4p16);Tg (5uas:epNTR-p2a-mcherry) zebrafish using an enhanced potency nitroreductase (epNTR)-mediated chemogenetic ablation system, which showed highly efficient ablation of pancreatic β-cells following treatment with low-dose metronidazole (MTZ). Using in vivo live imaging, we observed that sensory nerve endings and postsynaptic formation in the peripheral lateral line (PLL) were defective, followed by a disturbance in rheotaxis behavior without any locomotory behavioral changes. Despite defects in sensory nerves and elevated glucose levels, both reactive oxygen species (ROS) levels, a primary cause of DPN, and the number of ganglion cells, remained normal. Furthermore, we found that the activity of mTOR, a downstream target of IR signaling, was decreased in the PLL ganglion cells of the transgenic zebrafish. Our data indicates that peripheral neuropathy results from the loss of IR signaling due to insulin deficiency rather than hyperglycemia alone.